Another Generalized Closed Sets in Ideal Topological Spaces - O. Ravi; R. Asokan; A. Thiripuram (International Journal of Mathematics And its Applications, 2015)
Characterizations and properties of I_gδ-closed sets and I_gδ-open sets are given. A characterization of δ–normal spaces is given in terms of I_gδ-open sets.